(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the main factors contributing to the formation of psychological stability among future military leaders. Special attention is paid to the impact of negative ideas and social threats in modern conditions of information warfare and global instability. The article analyzes modern approaches to the development of sustainability, including the use of educational technologies, psychological and pedagogical methods and specialized programs. As a result, key factors are identified that can minimize the impact of negative phenomena on the personality of future military leaders.